2015
DOI: 10.1016/j.sbspro.2015.01.565
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of Speaking Anxiety in EFL Learners through Drama Techniques

Abstract: The study on drama and anxiety reduction was conducted with 24, 12 th grade students at a high school in Kozan, Turkey. The triangulation of the data was established with pre and post-tests, semi-structured pre and postinterviews, and student diaries. The teacher's reflections strengthened the qualitative aspect of the study. After six weeks of language and drama training, the drama techniques significantly lowered the speaking anxiety of EFL learners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 8 publications
6
54
1
3
Order By: Relevance
“…We can deduce from that, using drama techniques and role plays might help students to diminish their level of language anxiety in EFL classes. There has been conducted a research by Atas (2015) about using drama techniques to reduce language anxiety in EFL classes. She pointed out that drama helped to reduce speaking anxiety in foreign language classes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can deduce from that, using drama techniques and role plays might help students to diminish their level of language anxiety in EFL classes. There has been conducted a research by Atas (2015) about using drama techniques to reduce language anxiety in EFL classes. She pointed out that drama helped to reduce speaking anxiety in foreign language classes.…”
Section: Discussionmentioning
confidence: 99%
“…Mak (2011) used this scale while he was conducting his research named 'An exploration of speaking-in-class anxiety with Chinese ESL learners'. Atas (2015) used Turkish version of Horwitz's Foreign Language Classroom Anxiety Scale in her study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even in English as a foreign language setting, drama-based English is capable of making learners relaxed and confident (Shand, 2008;Coleman, 2005). Similarly, Atas (2014) found that the intervention of drama in learning English does help to lower the speaking anxiety of learners. A recent study conducted by Nath, Maslawati and Hamidah (2017) also corroborated this finding.…”
Section: Krashen's Affective Filter Hypothesismentioning
confidence: 93%
“…This shift of lesson objective has significantly reduced learners' level of apprehension while speaking. In addition, (20) conducted a study on using drama as a means to reduce learners' anxiety while speaking. Based on the feedback, he concluded that the use of drama indeed lowers the level of anxiety among learners and promote positive outcome and motivate learners to be continuously engaged in the process of language training.…”
Section: B Factors Affecting Speaking Skillsmentioning
confidence: 99%